PKM Peningkatan Kualitas Guru PAUD Dalam Pembelajaran Pendidikan Agama Islam Berbasis Pendidikan Inklusif di KecamatanSunggal Kabupaten Deli Serdang - Rizka Harfiani; Mavianti Mavianti (University of Muhammadiyah Sumatera Utara, 2019)
Islamic religious education is important given since early childhood, as a foundation for moral formation and the cultivation of religious values. Education is the right of every child, including children with special needs, who are entitled to services in the inclusive education system at all levels of education. PKM Improving the quality of PAUD teachers in learning Islamic Education (PAI) Based on inclusive education in Sunggal sub-district, Deli Serdang, this is done because there are still many PAUD teachers in the Sunggal sub-district who do not have inclusive understanding and application (PAI) for children early, so that it has an impact on the use of inappropriate learning methods, and this results in the development of children's abilities that are expected to not be achieved. The lack of competency of PAUD teachers in Sunggal sub-district is due to the teacher's educational background, which on average only graduates from non-PAUD Public and Undergraduate Schools. The method used in this PKM is to hold training activities on the application of PAI learning based on inclusive education for PAUD teachers (RA and TK.ABA), in collaboration with Branch Manager Aisyiyah Sunggal. Teachers are taught PAI materials for early childhood, as well as practical applications in applying PAI learning based on inclusive education with appropriate learning methods.